2005
DOI: 10.1158/1055-9965.epi-05-0068
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Calcium Intakes from Food or Supplements and Mammographic Breast Density

Abstract: Background: A better understanding of factors that affect breast density, one of the strongest breast cancer risk indicators, may provide important clues about breast cancer etiology and prevention. This study evaluates the association of vitamin D and calcium, from food and/or supplements, to breast density in premenopausal and postmenopausal women separately. Methods: A total of 777 premenopausal and 783 postmenopausal women recruited at two radiology clinics in Quebec City, Canada, in 2001 to 2002, complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 82 publications
(94 reference statements)
4
69
8
Order By: Relevance
“…In particular, Cho et al (2004) concluded from an analysis of pooled primary data from 10 cohort studies that optimal risk reduction for colorectal cancer necessitates high intake levels of both vitamin D and calcium. Berube et al (2005) studied the relation of separate and combined intakes of vitamin D and calcium by pre-menopausal women on mammographic breast density as a surrogate marker for breast cancer risk. They found that the negative association between dietary vitamin D intake and breast density tended to be stronger when calcium intake levels were higher and vice versa.…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Cho et al (2004) concluded from an analysis of pooled primary data from 10 cohort studies that optimal risk reduction for colorectal cancer necessitates high intake levels of both vitamin D and calcium. Berube et al (2005) studied the relation of separate and combined intakes of vitamin D and calcium by pre-menopausal women on mammographic breast density as a surrogate marker for breast cancer risk. They found that the negative association between dietary vitamin D intake and breast density tended to be stronger when calcium intake levels were higher and vice versa.…”
Section: Cancermentioning
confidence: 99%
“…The resulting increase in intracellular Ca 2 þ may conceivably activate proapoptotic intracellular signalling, similar to that caused by 1,25-(OH) 2 D 3 (Mathiasen et al, 2002). The effect of the apparent cross-talk between Ca 2 þ /CaR and 1,25-(OH) 2 D 3 /VDR signalling on cytosolic Ca 2 þ may explain, at least in part, how vitamin D and calcium together efficiently regulate neoplastic mammary gland cell growth in vivo (Berube et al, 2005;Lin et al, 2007).…”
Section: Cancermentioning
confidence: 99%
“…For example, alcohol has been shown to consistently increase breast cancer risk [1] through many proposed mechanisms, including the alteration of estrogen metabolism and receptor status and increased exposure to harmful metabolites that damage DNA [27•]. Other components of the diet, such as vitamin D and calcium, may influence breast density, which is a strong risk factor for breast cancer [28][29][30]. Also, certain nutrients may be more influential on breast cancer risk only after reaching a threshold that promotes tumor development; thus, the baseline rate of consumption in a population may dictate when associations are observed [31].…”
Section: Discussionmentioning
confidence: 99%
“…Randomized control trials demonstrated changes in breast density with intake of low-fat high carbohydrate diet. 70,71 Cross-sectional studies have shown calcium and vitamin D, [72][73][74][75][76] and vegetables 75,77 to be associated with lower breast density.…”
Section: Breast Composition and Radiographic Appearancesmentioning
confidence: 99%
“…It is also increasingly important that screened women with dense breasts are advised to avoid lifestyles such as alcohol intake and exogenous hormone use that have been shown to increase cancer risk in women with dense breast. Also, consumption of food species associated with lower breast density 22,72,75,77 and physical activity 78 is encouraged as these may mitigate their risk of developing breast cancer.…”
Section: Breast Composition and Radiographic Appearancesmentioning
confidence: 99%